2004
DOI: 10.1073/pnas.0404443101
|View full text |Cite
|
Sign up to set email alerts
|

RNA dynamics in live Escherichia coli cells

Abstract: We describe a method for tracking RNA molecules in Escherichia coli that is sensitive to single copies of mRNA, and, using the method, we find that individual molecules can be followed for many hours in living cells. We observe distinct characteristic dynamics of RNA molecules, all consistent with the known life history of RNA in prokaryotes: localized motion consistent with the Brownian motion of an RNA polymer tethered to its template DNA, free diffusion, and a few examples of polymer chain dynamics that app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
290
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(305 citation statements)
references
References 48 publications
(50 reference statements)
11
290
1
Order By: Relevance
“…coli strain DH5a-PRO (identical to DH5a-Z1) was generously provided by I. Golding of the University of Illinois, and contains two constructs: (i) PROTET-K133 carrying P LtetO-1 -MS2d-GFP [23], and (ii) a pIG-BAC (P lac/ara-1 -mRFP1-MS2-96bs) vector, carrying a 96 binding site array under the control of P lac/ara-1 [23].…”
Section: Cells Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…coli strain DH5a-PRO (identical to DH5a-Z1) was generously provided by I. Golding of the University of Illinois, and contains two constructs: (i) PROTET-K133 carrying P LtetO-1 -MS2d-GFP [23], and (ii) a pIG-BAC (P lac/ara-1 -mRFP1-MS2-96bs) vector, carrying a 96 binding site array under the control of P lac/ara-1 [23].…”
Section: Cells Plasmidsmentioning
confidence: 99%
“…When the reporter and target RNA are co-expressed, MS2d-GFP binds to the target RNA, forming a bright fluorescent spot. The RNA becomes visible during, or shortly after elongation [23]. Images of cells were taken from each slide every minute over two hours [7].…”
Section: Time-lapse Single-molecule Fluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the transient character of RNA transcripts, it has proved technically challenging to monitor in real time the transcription activity of a promoter within an individual prokaryotic cell (2)(3)(4). There exist various powerful in vitro methods for measuring RNA levels, including Northern blots, RT-PCR, and microarrays.…”
mentioning
confidence: 99%
“…In bacteria, the counting of individual mRNAs in single cells showed that transcriptional bursting, infrequent transcription events that produce many transcripts within a short period of time, Fusco et al 2003;reprinted, with permission, from Elsevier # 2003. ) was responsible for the variability in gene expression (Golding and Cox 2004;Golding et al 2005). Similarly, in the eukaryote Dictyostelium, transcription of an endogenous developmental gene, dscA, was observed to be expressed in discrete bursts of gene activity (Chubb et al 2006).…”
Section: Single Molecule Imaging Of Mrna In Gene Expressionmentioning
confidence: 99%